2017
DOI: 10.1016/j.celrep.2017.07.074
|View full text |Cite
|
Sign up to set email alerts
|

Composition and Control of a Deg/ENaC Channel during Presynaptic Homeostatic Plasticity

Abstract: SUMMARY The homeostatic control of presynaptic neurotransmitter release stabilizes information transfer at synaptic connections in the nervous system of organisms ranging from insect to human. Presynaptic homeostatic signaling centers upon the regulated membrane insertion of an amiloride-sensitive Deg/ENaC channel. Elucidating the subunit composition of this channel is an essential step toward defining the underlying mechanisms of presynaptic homeostatic plasticity (PHP). Here, we demonstrate that the ppk1 gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 63 publications
(108 reference statements)
4
24
0
1
Order By: Relevance
“…Multiple mechanisms have been proposed to explain the increase in Ca 2+ influx observed during the expression of PHP (Frank et al, 2006;Frank et al, 2009;Younger et al, 2013;Brusich et al, 2015;Muller et al, 2015;Kiragasi et al, 2017;Orr et al, 2017). For example, a presynaptic epithelial sodium channel (ENaC) and glutamate autoreceptor (DKaiR1D) have been implicated in promoting Ca 2+ influx during PHP, leading to the model that modulation of presynaptic membrane potential might increase influx through Cac channels (Younger et al, 2013;Kiragasi et al, 2017;Orr et al, 2017). On the other hand, Frank and colleagues found that the guanine exchange factor Ephexin signals through the small GTPase Cdc42 to promote PHP in a Cac-dependent manner, raising the possibility that it does so through actin-dependent accumulation of channel levels (Frank et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Multiple mechanisms have been proposed to explain the increase in Ca 2+ influx observed during the expression of PHP (Frank et al, 2006;Frank et al, 2009;Younger et al, 2013;Brusich et al, 2015;Muller et al, 2015;Kiragasi et al, 2017;Orr et al, 2017). For example, a presynaptic epithelial sodium channel (ENaC) and glutamate autoreceptor (DKaiR1D) have been implicated in promoting Ca 2+ influx during PHP, leading to the model that modulation of presynaptic membrane potential might increase influx through Cac channels (Younger et al, 2013;Kiragasi et al, 2017;Orr et al, 2017). On the other hand, Frank and colleagues found that the guanine exchange factor Ephexin signals through the small GTPase Cdc42 to promote PHP in a Cac-dependent manner, raising the possibility that it does so through actin-dependent accumulation of channel levels (Frank et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Так, ген ASIC2 (acid sensing ion channel subunit 2) кодирует кислотно-чувствительный ионный канал, принадлежащий к суперсемейству дегенеринов/ эпителиальных натриевых каналов (DEG / ENaC) [21,22]. В работе [23] была показана связь ASIC2 с развитием и метастазированием колоректального рака (CRC) за счет активации сигнального пути calcineurin/NFAT1 в условиях ацидоза [23].…”
Section: Discussionunclassified
“…However, it should be noted that other studies have reported a broader subcellular distribution of ASICs in individual central neurons, in contrast to synaptic enrichment [68]. Invertebrate DEG/ ENaCs have also been identified at synaptic sites in C. elegans and Drosophila [47,62], although the majority of localization data in these species has only been assessed by using the overexpression of tagged transgenes, and therefore, the subcellular distribution of native DEG/ENaC channels has yet to be determined in the majority of invertebrate species. In addition to the immunohistochemistry data, immunoprecipitation studies in heterologous expression systems have found that specific ASIC subunits interact with both pre-and postsynaptic proteins, including clathrin and PSD95 [67,69].…”
Section: Roles Of Deg/enac Channels In Synaptic Physiology and Neuronmentioning
confidence: 91%
“…More recently, several studies suggested that DEG/ENaCs also play an important modulatory role at the synapse in both vertebrate and invertebrate species [41,[46][47][48][49][50][51][52][53]. However, the exact cellular and physiological mechanisms that mediate the effects of DEG/ENaCs on synaptic physiology remain poorly understood.…”
Section: Introductionmentioning
confidence: 99%